Subgroup Analyses of Maraviroc in Previously Treated R5 HIV-1 Infection - Gerd Fätkenheuer; Mark Nelson; Adriano Lazzarin; Irina Konourina; Andy I. M. Hoepelman; Harry Lampiris; Bernard Hirschel; Pablo Tebas; François Raffi; Benoît Trottier; Nicholaos Bellos; Michael S. Saag; et al. (2008)
We conducted subanalyses of the combined results of the Maraviroc versus Optimized Therapy in Viremic Antiretroviral Treatment-Experienced Patients (MOTIVATE) 1 and MOTIVATE 2 studies to better characterize the efficacy and safety of maraviroc in key subgroups of patients.We analyzed pooled data from week 48 from the two studies according to sex, race or ethnic group, clade, CC chemokine receptor 5 (CCR5) delta32 genotype, viral load at the time of screening, the use or nonuse of enfuvirtide in optimized background therapy (OBT), the baseline CD4 cell count, the number of active antiretroviral drugs coadministered, the first use of selected background agents, and tropism at baseline. Changes in viral tropism and the CD4 count at treatment failure were evaluated. Data on aminotransferase levels in patients coinfected with hepatitis B virus (HBV) or hepatitis C virus (HCV) were also analyzed.A treatment benefit of maraviroc plus OBT over placebo plus OBT was shown in all subgroups, including patients with a low CD4 cell count at baseline, those with a high viral load at screening, and those who had not received active agents in OBT. Analyses of the virologic response according to the first use of selected background drugs showed the additional benefit of adding a potent new drug to maraviroc at the initiation of maraviroc therapy. More patients in whom maraviroc failed had a virus binding to the CXC chemokine receptor 4 (CXCR4) at failure, but there was no evidence of a decrease in the CD4 cell count at failure in such patients as compared with those in whom placebo failed. Subanalyses involving patients coinfected with HBV or HCV revealed no evidence of excess hepatotoxic effects as compared with baseline.Subanalyses of pooled data from week 48 indicate that maraviroc provides a valuable treatment option for a wide spectrum of patients with R5 HIV-1 infection who have been treated previously. (ClinicalTrials.gov numbers, NCT00098306 and NCT00098722.)